An Overview of Using Building Information Modelling (BIM) in Construction Management - Albtoosh, Ja’far A. Aldibat; Ahmad Tarmizi, Haron; AL-Btoush, Mohammed A. KA. (Universiti Malaysia Pahang, 2016)
Building information modeling (BIM) is one of the most impressive recent developments in the architecture, engineering, and construction (AEC) industry. Using BIM technology, gives you a 3 D virtual model of a building digitally constructed. This operation called a building information model, can be used for planning, design, construction, and operation of the project. It (AEC) parts to have a clear sight for any potential design. In this paper, we present an over view for BIM, case studies for researchers. The findings of this study concluded that there’s a great benefits provided by using BIM, and this usage will be reflected on the time and the cost of the projects.